Transcorneal electrical stimulation: impact on healthcare and future potential - Morimoto, Takeshi (Frontiers in Cell and Developmental Biology, 2025)
Transcorneal electrical stimulation (TES), a noninvasive therapeutic technique, has gained attention for its potential to treat retinal and optic nerve diseases. TES involves applying weak electrical currents via electrodes on the cornea to stimulate retinal ganglion cells (RGCs) without causing activation of photoreceptors, inducing phosphenes, and enabling the evaluation of inner retinal function. This is valuable for assessing residual retinal activity in patients with photoreceptor or RGC degeneration. Furthermore, TES has shown significant neuroprotective effects on RGCs and photoreceptors through mechanisms involving the upregulation of neurotrophic factors (e.g., insulin-like growth factor 1, brain-derived neurotrophic factor, and ciliary neurotrophic factor), reduction of inflammatory responses, and enhanced ocular blood flow. These findings are supported by extensive animal studies, showing its efficacy in mitigating retinal degeneration and optic nerve damage while promoting axonal regeneration. Clinically, TES has shown potential in improving visual function in diseases such as RP, optic neuropathies, and ischemic retinal conditions; however long-term benefits remain a challenge. Randomized controlled trials have indicated the safety and modest therapeutic effects of TES, suggesting its potential as an adjunct treatment for visual impairments. Moreover, TES may extend beyond ophthalmology into neurology. Because the retina is anatomically connected to the brain, TES can influence brain regions such as the visual cortex and hippocampus. Preliminary research proposes its potential for modulating brain, such as those with retinitis pigmentosa (RP). TES has demonstrated significant neuroprotective effects in networks, cognition, and emotional pathways, offering hope for treating neurodegenerative diseases such as Alzheimer’s and Parkinson’s disease. In summary, TES represents a versatile and promising therapy for retinal and neurological disorders, and ongoing advancements will likely expand its applications in clinical practice. Further studies are warranted to optimize its parameters, enhance its efficacy, and explore its full therapeutic potential.